Social Media’s Role in Shaping Contemporary News Discourse on the 2023 Election Petition Cases in Enugu State - Ajibo, Chioma Blessing; Okpoko, Chinwe Catherine (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study investigates the impact of social media on the discourse surrounding the 2023 Election Petition Cases in Enugu state. The main objective is to understand how social media influences public perception and discourse during critical political events. Employing the Agenda-Setting Theory and Social Identity Theory, the study explores the agenda-setting function of social media and its role in reinforcing existing beliefs, polarization, and shaping opinions. The methodology involves a multifaceted approach comprising social media content analysis, sentiment analysis, and surveys. Data collection spans platforms like Facebook, Twitter, Instagram, YouTube, and blogs. Statistical analyses and clustering techniques are employed to validate hypotheses regarding the frequency of discussions, polarization of opinions, and exposure to diverse viewpoints. The results reveal a strong correlation between social media discussions’ frequency and the prominence of specific allegations related to the election cases, validating the influence of social media in agenda-setting. Sentiment analysis highlights polarization within discourse, showcasing divergent viewpoints on the legitimacy of the election outcome. Survey findings indicate the reinforcement of existing beliefs among users, restricting exposure to diverse perspectives. The study concludes that social media significantly shapes public discourse during critical events, emphasizing the need for interventions. Recommendations include media literacy programs, platform regulations for balanced content exposure, promotion of diverse content, and advocating for responsible social media usage. These recommendations aim to foster a healthier online discourse, encourage informed opinions, and enhance democratic participation while mitigating the negative impacts of social media on public perception and discourse.